1998
DOI: 10.1111/j.1440-1819.1998.tb01002.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol effect on sleep electroencephalography by fast Fourier transformation

Abstract: The influence of alcohol (ethanol) on sleep was investigated in 10 men. Polysomnography (PS) was recorded on a baseline night (BL-N) and an ethanol (0.8 g/kg) night (Et-N). On visual score rapid eye movement (REM) sleep was reduced, REM latency was prolonged on Et-N as compared to BL-N. Using the fast Fourier transformation method, electroencephalographic power density of REM sleep in S frequencies band and in the 10-12 Hz range of non-REM sleep were enhanced. REM sleep and non-REM sleep changes were prominent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 6 publications
0
9
0
1
Order By: Relevance
“…Although the morning and afternoon mood scores were significantly worse following the alcohol condition, these results may have been driven in part by fatigue resulting from alcohol's sleep‐disturbing effects [36,71–73].…”
Section: Discussionmentioning
confidence: 91%
“…Although the morning and afternoon mood scores were significantly worse following the alcohol condition, these results may have been driven in part by fatigue resulting from alcohol's sleep‐disturbing effects [36,71–73].…”
Section: Discussionmentioning
confidence: 91%
“…From the initial short‐list of 27 publications , 7 were completely excluded from the data analysis due to methodological limitations, duplication of data, incomplete data, and other issues affecting the veracity of the data (Chan et al., ; Gresham et al., ; Knowles et al., ; Kobayashi et al., ; Stone, ; Williams and Salamy, ; Yules et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…These results suggest that ethanol does not seem to change the quality of human SWS throughout the entire night, in spite of changes in EEG power spectrum. In this regard, we previously investigated the effect of ethanol on EEG power spectrum by fast Fourier transformation [35]. Our results in that study indicated that alcohol enhanced the ‰ and frequencies during REM sleep of the fourth sleep cycle.…”
Section: Discussionmentioning
confidence: 85%